2017
DOI: 10.1016/j.dsr2.2016.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Evidence and age estimation of mass wasting at the distal lobe of the Congo deep-sea fan

Abstract: International audienceOn continental margins, sulfate reduction occurs within the sedimentary column. It is coupled with the degradation of organic matter and the anaerobic oxidation of methane. These processes may be significantly disturbed by sedimentary events, leading to transient state profiles for the involved chemical species. Yet, little is known about the impact of turbidity currents and mass wasting on the migration of chemical species and the redox reactions in which they are involved. Due to its co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 72 publications
(105 reference statements)
1
5
0
Order By: Relevance
“…As an alternative explanation, Zabel and Schulz (2001) suggested that the S-shape is the result of down slope transport several hundred years ago of sliding sediment blocks with retained stratigraphy. This interpretation was supported by a recent study from the same deep sea fan off the Zaire River by Croguennec et al (2017) who found a sulfate-free, methane-rich sediment section sandwiched in between two sulfatic zones. Similar observations of down slope mass transport within the past hundreds of years have been made in other deep sea fans with high sedimentation rates, e.g., in the Bay of Bengal (Hong et al, 2014).…”
Section: Se Atlantic Continental Slopesupporting
confidence: 57%
“…As an alternative explanation, Zabel and Schulz (2001) suggested that the S-shape is the result of down slope transport several hundred years ago of sliding sediment blocks with retained stratigraphy. This interpretation was supported by a recent study from the same deep sea fan off the Zaire River by Croguennec et al (2017) who found a sulfate-free, methane-rich sediment section sandwiched in between two sulfatic zones. Similar observations of down slope mass transport within the past hundreds of years have been made in other deep sea fans with high sedimentation rates, e.g., in the Bay of Bengal (Hong et al, 2014).…”
Section: Se Atlantic Continental Slopesupporting
confidence: 57%
“…Additionally, numerous sedimentological and organic geochemical data were obtained during the shore-based studies on the 145 sediment cores collected in different parts of the Congo turbidite system, from the canyon head to the terminal lobe complex, by ca. 5000 m of water depth (Droz et al, 1996(Droz et al, , 2003Gervais et al, 2001;Babonneau, 2002;Babonneau et al, 2002Babonneau et al, , 2004Babonneau et al, , 2010Ferry et al, 2004;Migeon et al, 2004;Bonnel, 2005;Treignier, 2005;Marsset et al, 2009;Rabouille et al, 2009Rabouille et al, , 2017aRabouille et al, , 2017bBaudin et al, 2010Baudin et al, , 2017aBaudin et al, , 2017bPicot, 2015;Stetten et al, 2015;Picot et al, 2016Picot et al, , 2019Croguennec et al, 2017;Méjanelle et al, 2017;Pastor et al, 2017;Pozzato et al, 2017;Schnyder et al, 2017;Taillefert et al, 2017). The resulting data allows a good description and understanding of the entire Congo turbidite system.…”
Section: Summary Of Recent Studies On the Congo Deep-sea Fanmentioning
confidence: 99%
“…13% of the deposits of the lobe complex (Dennielou et al, 2017). In situ mass wasting, slumps and debrites characterize the whole lobe complex (Croguennec et al, 2017;Dennielou et al, 2017). High-resolution bathymetry using ROV shows extensive block on the edges at the channel mouth indicating that sliding occurs continuously in the lobe build-up.…”
Section: Sedimentary Architecturementioning
confidence: 99%
“…Talling et al., ), and so it is assumed that the cores are composed entirely of turbidites and do not include appreciable hemipelagic sediment. It is also assumed that there has been no post‐depositional erosion, reworking or mass wasting, though these processes do occur even in distal parts of submarine fans (Croguennec et al., ; Dennielou et al., ). While some data indicate that event‐bed geometries in submarine‐fan deposits can be more complex (Deptuck et al., ; Jobe et al., 2017b), it is also assumed that core data accurately record the event count n and that all events spread evenly across the fan/lobe.…”
Section: Estimation Of Turbidity Current Volume and Recurrencementioning
confidence: 99%